Identifikasi Virus Penyebab Penyakit Mosaik pada Tanaman Melon (Cucumis melo L.) di Bali - RIZWAN FEBIANTA BRAHMANA; TRISNA AGUNG PHABIOLA; I GEDE RAI MAYA TEMAJA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
Identification of Viruses that Causes Mosaic Diseases in Melons(Cucumis melo L.) in Bali The aims of this research was to identify of some virus that infects melons in Bali. The first step of this research was to take samples in Jembrana Regency, TabananRegency, Gianyar Regency, Denpasar City, and Badung Regency. The next step wasdoing virus detection at Laboratory of Plant Diseases, Faculty of Agriculture, UdayanaUniversity. Variations of symptoms found in the field were mosaic, yellow leaves,malformations, and burning spots on the leaves. The percentage of virus attacks inGianyar and Badung was the highest percentage (60.00%), Jembrana (57.14%),Denpasar (42.85%), and Tabanan (37.50%). To know type of virus that causes thisdisease, molecular identification was conducted. Extraction was the first step to gettotal RNAs from symptomatic leaves. Total RNAs was transcribed intoComplementary (c) DNAs using reverse transctiption-polymerase chain reaction (RTPCR)technique. Polymerase chain reaction (PCR) was conducted using cDNA and three primer pairs of CABYV-489-F/Pol-G-R, MABYV-262-F/Pol-G-R andCIFOR/CIREV. Primers would be use to amplified a part of coat protein. CABYV489-F/Pol-G-Rand MABYV-262-F/Pol-G-R is specific primer, and CIFOR/CIREV would be use to amplified gene of Potyvirus. Based on the results of molecular with PCR it was found that melons in Bali were positively infected with viruses from thePotyvirus group with a size of around 683 bp in samples from Gianyar and Denpasar.